Pengaruh Dana Desa Terhadap Pendapatan Masyarakat Di Desa Pandankrajan, Kecamatan Kemlagi, Kabupaten Mojokerto - Yuli Setyaningsih; Siti Sundari (Journal of Economic, Bussines and Accounting (COSTING), 2023)
The community empowerment program is still minimal and the economic level of the villagers is still low because the average villager's profession as a farmer forms the basis of this research. The purpose of this study was to test and prove the effect of physical development and community empowerment on the income of the people of Pandankrajan Village. The population used is the Pandankrajan village community of 2900 people. Purposive sampling was used to select a sample and obtain 97 respondents who met the requirements, namely the headman, village secretary, finance officer, planning officer, Village Consultative Body, head of government, head of welfare, head of service, head of hamlet, head of RT and RW, and people who are members of savings and loans. This study uses primary data. The primary data in this study were taken through direct distribution of questionnaires. The analysis technique used is SEM-PLS. The results showed that community empowerment had a positive and significant impact on people's income, because the empowerment program provided by the Pandankrajan village government had a better impact on the people's economy. Meanwhile, physical development has a negative and significant impact on people's income, so that increased physical development actually reduces people's income. Keywords: Physical Development, Community Empowerment, Community Income